Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/iub.1882
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis: Surviving and Indulging in an Unwelcoming Host

Abstract: More than a century has passed since the identification of Mycobacterium tuberculosis (Mtb) as the causative agent of tuberculosis (TB), we still are nowhere close to eradicating this deadly disease. Moreover, emergence of new drug-resistant strains has further complicated the situation, making it even more difficult to treat by conventional therapy regimens. Humans are the only reservoir for the existence and propagation of Mtb, which suggests that its latent forms will be most difficult to eradicate, till th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
(76 reference statements)
0
8
0
1
Order By: Relevance
“…Studies involving nonhuman primate TB granulomas showed that M1 polarization is related to a favorable disease outcome (22). During infection, TB granulomas are the active sites of host-Mtb interactions, where Mtb develops mechanisms to resist host protective immunity, and the host localizes the condition (23)(24)(25)(26). The alveolar macrophages representing bacterial permissiveness are associated with fatty acid boxidation, when compared with glycolytically active interstitial macrophages (27).…”
Section: Overview Of Immunometabolism In Host-mtb Infectionsmentioning
confidence: 99%
“…Studies involving nonhuman primate TB granulomas showed that M1 polarization is related to a favorable disease outcome (22). During infection, TB granulomas are the active sites of host-Mtb interactions, where Mtb develops mechanisms to resist host protective immunity, and the host localizes the condition (23)(24)(25)(26). The alveolar macrophages representing bacterial permissiveness are associated with fatty acid boxidation, when compared with glycolytically active interstitial macrophages (27).…”
Section: Overview Of Immunometabolism In Host-mtb Infectionsmentioning
confidence: 99%
“…In Indian continent TB is oldest communicable, fatal contagious disease that is deeply rooted among Indian population. TB has a history of being together with mankind for very long and was first discovered by Hippocrates in 400 BC [2]. History has evidence that many emperors died and many empire demolished due to this fatal disease in India [3][4][5] .The first written documents describing TB, dating back to 3300 and 2300 years ago, were found in India and in China respectively [6].…”
Section: Historymentioning
confidence: 99%
“…Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis (Mtb), is the leading cause from a single infectious agent worldwide. Mtb, a pathogenic bacterium species of the family Mycobacteriaceae , can attack the lung of people and spread in the population through the droplets from the throat of an active TB infection patient (Mishra and Surolia, 2018). Millions of people continue to fall sick with TB each year.…”
Section: Introductionmentioning
confidence: 99%